Gender differences of basketball players aged 12-13 years according to the response to a moving object - L.S. Frolova; S.O. Kovalenko; Yu.O. Petrenko; A.A. Tymofeev; P.M. Gunko; I.M. Khomenko; O.A. Atamas; L.A. Nechyporenko; D.L. Nechyporenko (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Purpose: The study aims at the determining gender differences of basketball players aged 12-13 years in response to an object in motion that determines the predominance of excitation and inhibition processes. Material: The participants of the study are 58 basketball players aged 12-13 years, 35 are male basketball players and 23 are female. Male basketball players had 4-5-year training experience, female had 1,5-2-year experience. All athletes had normal visual acuity and were healthy at the time of the study. Young basketball players were informed about the purpose of the study. The computer program containing visual stimuli, moving with acceleration from different points of the monitor was used for testing. Results: The deviations from the target data as well the pole were taken into consideration. It demonstrated the predominance of excitation and inhibition processes of basketball players of different sexes. The response accuracy to visual stimuli without taking into account the pole during perception with the left eye and the right eye is shown. Conclusions: It was found out that the females' response accuracy during monocular perception is more closely related to the response accuracy during binocular imaging, whereas the role of the males' leading eye is increased during perception of objects from a convenient side. This may indicate the peculiar reactions under the conditions of double perception of objects in solving complex spatial problems.